A Framework on Exploring Primary School English Language Teachers’ Perceptions of their Continuing Professional Development in Malaysia - Elaine Ling Ling Pang; David Wray (Athens Journal of Education, 2017)
The national concern to improve in-service training (INSET) for English language teachers in Malaysia has led to the need to reshape continuing professional development (CPD). CPD providers in Malaysia tend to conduct training using the cascade model and teachers are hardly consulted about their needs or learning preferences. This is likely to have a significant impact on the quantity and quality of INSET for teachers in a top-down national priority driven system. The research to be reported in this paper focuses on the perceptions of a group of Malaysian primary school English language teachers of their INSET experiences, the CPD models they prefer, and their perceptions of the effect of CPD on their classroom practice. The research also aims to identify their future expectations of INSET in terms of their professional development needs and their pupils’ needs. Qualitative survey research was undertaken using profile questionnaires, focus group interviews and individual interviews, followed by an online survey of all research participants. The researcher followed the CPD journey of three groups of primary school educators, selected using convenience sampling and purposeful sampling. This paper suggests a framework to investigate teachers’ views about their needs. This would shed light on how CPD providers can enhance teachers’ professional development and thus student achievement.